2011
DOI: 10.1016/j.partic.2010.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of formulation of alginate beads on their mechanical behavior and stiffness

Abstract: Effect of formulation of alginate beads on their mechanical behavior and stiffness. AbstractThe aim of this work was to determine the effect of formulation of alginate beads on their mechanical behavior and stiffness when compressed at high speed. The alginate beads were formulated using different types and concentrations of alginate and gelling cations and were produced using an extrusion-dripping method. Single wet beads were compressed at a speed of 40 mm/min, and their elastic limits were investigated, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
89
1
10

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(120 citation statements)
references
References 14 publications
8
89
1
10
Order By: Relevance
“…In general, the stiffness of alginate magnetic beads may be considered to depend on the degree of cross-linking. Higher alginate concentration produces stiffer beads due to the increase in cross-linking density [14]. Fig.…”
Section: Compression Test Of Pva-alginate Magnetic Beadsmentioning
confidence: 97%
See 1 more Smart Citation
“…In general, the stiffness of alginate magnetic beads may be considered to depend on the degree of cross-linking. Higher alginate concentration produces stiffer beads due to the increase in cross-linking density [14]. Fig.…”
Section: Compression Test Of Pva-alginate Magnetic Beadsmentioning
confidence: 97%
“…The compression tests of the beads were performed using a Texture Analyser TA-XT2i (Hounsfield Corp, UK) attached with a 25 N force transducer. Spherical beads were used in the study and each bead is immersed in water and placed onto a platform as reported by Chan et al [14]. The bead was compressed by a flat end probe up to a deformation (ratio of displacement to initial bead diameter) equivalent to 30% from initial size at a test speed of 40 mm/min at room temperature of 25 ± 1 • C. In order to ensure reproducible results; the number of beads compressed per sample was kept to 3.…”
Section: Compression Test Of Pva-alginate Magnetic Beadsmentioning
confidence: 99%
“…The value for the surface tension of the alginate based solutions at 15 g/L was obtained from Chan et al (2011a) and considered constant for all seven samples.…”
Section: Mixture Propertiesmentioning
confidence: 99%
“…Chan et al (2011a) have shown that low viscosity of the filler leads to high shrinkage factor. In accordance to what was previously found, this trend is also observed in the present work as can be seen in Fig.…”
Section: Granules Size and Shapementioning
confidence: 99%
See 1 more Smart Citation